Validation of Fear of Falling and Balance Confidence Assessment Scales in Persons With Dystonia. Issue 4 (October 2017) - Boyce, Melani J.; Lam, Lawrence; Chang, Florence; Mahant, Neil; Fung, Victor S. C.; Bradnam, Lynley
Abstract : Background and Purpose: Falls are problematic for people living with neurological disorders and a fear of falling can impact on actual falls. Fear of falling is commonly assessed using the Falls Self-Efficacy Scale International (FES-I) or the Activities-specific Balance Confidence (ABC) Scale. These scales can predict risk of falling. We aimed to validate the FES-I and the ABC in persons with dystonia. Methods: We conducted an online survey of people with dystonia, collecting information on demographics, 6-month falls history, dystonia disability, and the FES-I and ABC scales. Scales were validated for structural validity and internal consistency. We also examined goodness-of-fit, convergent validity, and predictive validity, and determined cutoff scores for predicting falls risk. Results: Survey responses (n = 122) showed that both FES-I and ABC scales have high internal validity and convergent validity with the Functional Disability Questionnaire in persons with dystonia. Each scale examines a single factor, fear of falling (FES-I) and balance confidence (ABC). At least one fall was reported by 39% of participants; the cutoff value for falls risk was found to be 29.5 and 71.3 for the FES-I and the ABC respectively. Discussion and Conclusions: The FES-I and the ABC scales are valid scales to examine fear of falling and balance confidence in persons with dystonia. Fear of falling is high and balance confidence is low and both are worse in those with dystonia who have previously fallen. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A182 ). Abstract : Supplemental Digital Content is Available in the Text.